Finite‐Sized One‐Dimensional Silica Microstructures (Rods): Synthesis, Assembly, and Applications. Issue 4 (17th February 2017) - Sharma, Jaswinder
Abstract: Colloidal silica structures are very important for applications such as superhydrophobic, oleophobic, icephobic, and anti‐biofouling coatings, polymer–ceramic or metal–matrix composites, photon management, catalyst support, and drug delivery. In addition to various types of silica structures, a unique structure—silica rods—has been synthesized by employing the emulsion droplets made by adding water and citrate to polyvinylpyrrolidone pentanol solution. While significant progress has been made in modifying rod shape and chemistry, in rod assembly, and in rod applications, however, no review article has discussed the progress in this field. This Focus Review intends to highlight the developments in the synthesis, assembly, and application of these rods, and discuss the remaining challenges for precise control of size and shape, possible solutions, and potential applications. Abstract : The synthesis, modification, assembly, and applications of a new class of microstructures—silica rods—have been reviewed. The focus is on finding new ways to address the challenges of precisely controlling the size and shape, and on a path forward for potential applications.